Metodika stanovení ceny letové hodiny letounu - Cichy, Radim (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Náplní bakalářské práce je specifikace jednotlivých činností a položek v oblasti provozních a fixních nákladů, souvisejících s kalkulací ceny za letovou hodinu. Na základě jednotné metodiky, je u vybraných nejčastěji využívaných letounů, používaných k získání pilotní kvalifikace pro jednomotorové a vícemotorové letouny s pístovými motory, stanovena reálná cena letové hodiny. Výsledná částka je dále porovnána s nabízenými cenami komerčních společností v ČR.

The bachelor's thesis is a specification of individual activities and items in the field of operating and fixed costs related to the calculation of the price per flight hour. Based on a unified methodology, the real price of the flight hour is determined for selected most commonly used aircraft used to obtain pilot ratings for single engine and multi-engine piston engine airplanes. The resulting amount is also compared with the prices offered by commercial companies in the Czech Republic.
Methodology of price determination of airplane flight hours
Keywords: metodika; výpočet; letoun; cena; letová hodina; provozní náklady; fixní náklady; methodology; calculation; airplane; price; flight hour; operating cost; fixed costs